A „nagy felsóhajtás zsoltára”. A Zsolt 124 magyarázata - KUSTÁR, Zoltán (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2019)
The Psalm of the Great Sigh of Relief. Interpretation of Psalm 124. The study examines Psalm 124, one of the greatest gems of the biblical psalm-poetry. After briefly expounding the metre, the genre and the poetic structure, the author dates the poem, analyzes the role of the Psalm in its immediate literary con-text, and provides linguistic, formal, tradition-historical and theological analysis passage by passage. The author regards the Psalm as one of the post-exilic impressions of the Zion theology along with the collection of Psalms 120–134 which was formed around 400 BCE. Regarding the form of the poem, it is masterfully structured. Traces of later adaptations and additions cannot be proven unequivocally. The theological specialties of the poem are the articulation of the preventive providence of God, the thanksgiving and the consistent trust toward the God of Israel. The Psalm fits in well with the collections of Psalms 123–125 and Psalms 123–130, where the preceding Psalm of lament continues with the themes of thanksgiving and teaching, and goes further toward the theme of salvation of the end times.